2005
DOI: 10.1016/j.tourman.2004.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Innovation activity in the hotel industry: Evidence from Balearic Islands

Abstract: The paper provides empirical evidence on technological activity in the Spanish service sector, in particular for the tourist accommodation in the Balearics. The study wants to fulfil the lack of analyses in the field of tourism. Commonly, the study of innovation activity has been carried out from a manufacture perspective, for that reason the paper discusses the precise definition of innovation in accommodation services. The data refer to a large representative sample of hotels in Balearic Islands (Spain), pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
161
0
11

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 275 publications
(189 citation statements)
references
References 48 publications
(59 reference statements)
9
161
0
11
Order By: Relevance
“…Yet, estimating the scale of innovation in tourism is problematic (cf. Hertog et al, 2011;Camison, 2011;Krizaj, 2012; Orfila-Sintes, Crespi-Cladera and Martinez-Ros, 2005). This reflects significant unresolved differences of opinion on how it should be measured and on the factors that influence its form in various sectors, locations and over time (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, estimating the scale of innovation in tourism is problematic (cf. Hertog et al, 2011;Camison, 2011;Krizaj, 2012; Orfila-Sintes, Crespi-Cladera and Martinez-Ros, 2005). This reflects significant unresolved differences of opinion on how it should be measured and on the factors that influence its form in various sectors, locations and over time (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Drawing upon the work of Jacob et al (2003) and Orfila-Sintes et al (2005), three dimensions of innovation in hotels are identified: products, processes and market/organisational (Sundbo & Galloouj, 1998). The first dimension relates to product enhancement and differentiation, which aim to improve customer experiences by creating new combinations or sets of services (Norman, 1984), including more environmentally sustainable products (Williams & Shaw, 1998).…”
Section: Migration Experience and Innovation Performancementioning
confidence: 99%
“…The latter indicates the dependence of the industry on changes such as fluctuations in demand resulting from terrorism, disruption to flights, or changing visa requirements. The two main foci of internal changes relate to IT and the refurbishment of different areas of the hotel; the former reflects the information intensity of hotel business (Orfila Sintes et al, 2005), and the scale of technological changes, while the latter reflects the fact that many, or even most, London hotels are housed in relatively old buildings.…”
Section: Product Enhancement and Differentiationmentioning
confidence: 99%
“…Thus, it is necessary for tourism companies to face the development of new technologies and, above all, structural and organisational innovation (Stamboulis & Skayannis, 2003). However, researchers still stress that research in the field of innovation in tourism is very low, with few existing studies containing empirical analysis (e.g., Gomezelj Omerzel, 2014;Hjalager, 2010;Novelli, Schmitz, & Spencer, 2006;Orfila-Sintes, Crespi-Cladera, & Martinez-Ros, 2005;Sundbo, OrfilaSintes, & Sorensen, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We agree that the relation between innovation and performance is a multifaceted issue and requires further research. Authors from our second group (Bellou & Andronikidis, 2009;Chang, Gong, & Shum, 2011;Martinez-Ros & Orfila-Sintes, 2012;Orfila-Sintes et al, 2005;Sundbo et al, 2007) focused more on the key antecedents of innovativeness (human resource management practices, the importance of employees and training, organisational culture, organisational climate, leadership characteristics, business strategy, R&D departments, market strategy, environment, and so on). Crépon, Duguet, and Mairesse (1998) emphasised that firms invest in research not only to improve innovation activities but also, and especially, because of the contribution of such efforts to firm productivity and, consequently, to firm performance.…”
Section: Introductionmentioning
confidence: 99%